O teoretycznych i metodologicznych podstawach badań empirycznych w dydaktyce literatury = On the theoretical and methodological foundations of the empirical research in the didactics of literature - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The paper formulates and attempts to solve some crucial theoretical and methodological problems constituting the foundations of the empirical research in the didactics of literatura. The paper, among other things, presents the context of discovering a theory and the context of proving it, the relationship of theory to fact, the application of the empirical research, the falsification of the theory, the categories of empirical research. The author deals with the prob&ms of humanistic interpretation in the didactics of literatura and constructs the general model of the empirical research within thie discipline.
Keywords: dydaktyka literatury; badania empiryczne